Molecular prevalence of Toxoplasma gondii in sheep from Isfahan, Iran as detected in heart samples by loop-mediated isothermal amplification (LAMP) - RAIESZADEH, H.; NOAMAN, V.; RAZMI, G.; JAMSHIDI, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
Toxoplasmosis is considered an important zoonosis that affects not only humans but also livestock worldwide. Small ruminants are important intermediate hosts of T. gondii. This study aimed to determine the molecular prevalence of T. gondii in the slaughtered sheep by loop-mediated isothermal amplification (LAMP) assay in Isfahan, Iran. A total of 250 sheep heart samples were collected from five different slaughterhouses in Isfahan, Iran, from October 2017 to May 2018. The LAMP assay was optimized targeting the sequence of 529 bp DNA fragments of T. gondii and detected T. gondii DNA in 96.4% (241/250) of samples. A significantly higher prevalence of T. gondii was recorded among female animals as compared to male animals (p ≤ 0.05). No statistically significant difference in T. gondii prevalence was noted between the seasons, type of animals, and age groups (p >0.05). To the best of our knowledge, the current study is the first to use the LAMP assay to determine the prevalence of T. gondii in sheep in Iran. The prevalence obtained in this study by the LAMP assay was higher than the prevalence reported by previous studies that used other methods. This study suggests that sheep meat may play a more prominent role as a source of infection of humans and the LAMP technique can be a recommended tool for accurate diagnosis of toxoplasmosis.